2018
DOI: 10.1175/jcli-d-18-0365.1
|View full text |Cite
|
Sign up to set email alerts
|

A Nonstationary ENSO–NAO Relationship Due to AMO Modulation

Abstract: Many previous studies have demonstrated a high uncertainty in the relationship between El Niño–Southern Oscillation (ENSO) and the North Atlantic Oscillation (NAO). In the present work, decadal modulation by the Atlantic multidecadal oscillation (AMO) is investigated as a possible cause of the nonstationary ENSO–NAO relationship based on observed and reanalysis data. It is found that the negative ENSO–NAO correlation in late winter is significant only when ENSO and the AMO are in phase (AMO+/El Niño and AMO−/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 70 publications
3
32
0
Order By: Relevance
“…For example, it is reported that variation in boreal spring NAO influenced the subsequent intensity of the EASM from 1979 to 2006 (Wu et al, 2009). The linkage between the EASM and NAO has been further explored but on the interdecadal scale (Wu and Lin, 2012;Zuo et al, 2013), and it is suggested that the preceding spring NAO dominated the relationship of the NAO-EASM more than the simultaneous summer NAO; a similar result is seen in Zheng et al (2016). Xu et al (2013) presented the previous boreal summer NAO as significantly influencing the following September rainfall over central China.…”
Section: Introductionmentioning
confidence: 83%
“…For example, it is reported that variation in boreal spring NAO influenced the subsequent intensity of the EASM from 1979 to 2006 (Wu et al, 2009). The linkage between the EASM and NAO has been further explored but on the interdecadal scale (Wu and Lin, 2012;Zuo et al, 2013), and it is suggested that the preceding spring NAO dominated the relationship of the NAO-EASM more than the simultaneous summer NAO; a similar result is seen in Zheng et al (2016). Xu et al (2013) presented the previous boreal summer NAO as significantly influencing the following September rainfall over central China.…”
Section: Introductionmentioning
confidence: 83%
“…Interactions between the cycles described above and their resultant in uence on climate are welldocumented. For example, AMO is known to weaken the effects of ENSO, NAO, and AO during its positive phase and amplify them during its negative phase (Zhang et al 2012;Kang et al 2014;Park and Li 2019;Zhang et al 2019;Chen et al 2020). Other climate oscillations thought to in uence weather only weakly in uence climate in the region, or occur with frequencies of hundreds or thousands of years, well beyond the instrumental records examined in this study (Mann et al 1995;Domínguez-Villar et al 2017).…”
Section: Quasi-biennial Oscillation (Qbo)mentioning
confidence: 59%
“…AMO positive phases have been associated with several changes in climate, such as decreased precipitation, increased temperature, and droughts in North America (En eld et al 2001;Hodson 2005, 2007;Nigam et al 2011). However, in reference to extreme temperatures and precipitation, the AMO has a more prevalent impact on North America by modulating the effects of other climate phenomena (Mo et al 2009;Zhang et al 2012;Kang et al 2014;Park and Li 2019;Zhang et al 2019).…”
Section: Atlantic Multidecadal Oscillation (Amo)mentioning
confidence: 99%
“…Another important factor that can impact the ENSO teleconnection to the North Atlantic is decadal variability such as the Pacific Decadal Oscillation (PDO) (Rao et al, 2019) and the Atlantic Mutidecadal Oscillation (AMO) (Zhang et al, 2018).…”
Section: The Tropospheric Link Between the North Pacific And The Nortmentioning
confidence: 99%